PENGARUH EDUKASI PENCEGAHAN HIV/AIDS MELALUI MEDIA TIKTOK TERHADAP TINGKAT PENGETAHUAN DAN SIKAP SISWA JURUSAN TEKNIK JARINGAN KOMPUTER DI SMK MUHAMMADIYAH 3 TANGERANG SELATAN - Kapahang, Osty Histry; Wahyudin, Muhammad Didin; Handoko, Wisnu; Pitriani, Pipit; Suryadi, Suryadi (NURSING ANALYSIS: Journal of Nursing Research, 2025)
ABSTRACT HIV/AIDS is a disease that interferes with the human immune system. Based on the World Bank (2023), in 2021 HIV cases in Indonesia continue to increase by 0.2%, while in adolescents according to Indonesia's health profile (2021), 14-19 years old have increased from 2.9% to 3.1%. The high number of HIV/AIDS cases requires preventive measures. To increase knowledge and attitudes about HIV/AIDS prevention, education can be carried out through TikTok videos. The purpose of this study is to determine the effect of providing HIV/AIDS prevention education through TikTok media on the level of knowledge and attitude of students at SMK Muhammadiyah 3 South Tangerang. The research method used in this study is a quantitative research method with a type of Pre-Experimental research in the form of The One Group Pretest-Posttest design. The population in this study is all students majoring in TKJ which totals 94 students. Sampling uses the total sampling technique. The analysis of the research results used the Wilcoxon test. The instrument used in this study used a questionnaire about HIV/AIDS. The results of the study obtained a P-Value value of 0.000 for the level of knowledge and a P-Value value for attitude of 0.000, the results showed that there was a difference in the level of knowledge before and after being given an educational intervention for HIV/AIDS prevention through tiktok media and there was a difference in attitudes before and after being given an educational intervention for HIV/AIDS prevention through tiktok media. Therefore, it can be concluded that there is an influence of HIV/AIDS prevention education through tiktok media on the level of knowledge and attitude of students of the Department of Computer Network Engineering at SMK Muhammadiyah 3 South Tangerang. The suggestions from the results of this study are expected after being given health education about HIV/AIDS so that adolescents can get good information and carry out early prevention of HIV/AIDS infectious diseasesABSTRAKHIV/AIDS merupakan penyakit yang mengganggu sistem kekebalan tubuh manusia. Berdasarkan World Bank (2023) pada tahun 2021 kasus HIV di Indonesia terus meningkat sebanyak 0.2%, sedangkan pada remaja menurut profil kesehatan Indonesia (2021) 14-19 tahun mengalami peningkatan dari 2.9% menjadi 3.1%. Tingginya kasus HIV/AIDS memerlukan tindakan pencegahan. Untuk meningkatkan pengetahuan dan sikap tentang pencegahan HIV/AIDS dapat dilakukan edukasi melalui video tiktok. Tujuan penelitian ini adalah untuk mengetahui pengaruh pemberian edukasi pencegahan HIV/AIDS melalui media tiktok terhadap tingkat pengetahuan dan sikap siswa di SMK Muhammadiyah 3 Tangerang Selatan. Metode penelitian yang digunakan pada penelitian ini adalah metode penelitian kuantitatif dengan jenis penelitan Pre Eksperimental dengan bentuk The One Group Pretest-Posttest design. Populasi pada penelitian ini adalah semua siswa jurusan TKJ yang berjumlah 94 siswa/siswi. Pengambilan sampel menggunakan teknik total sampling. Analisis hasil penelitian menggunakan uji Wilcoxon. Instrument yang digunakan dalam penelitian ini menggunakan kuesioner tentang HIV/AIDS. Hasil penelitian diperoleh nilai P-Value tingkat pengetahuan sebesar 0.000 dan nilai P-Value sikap sebesar 0.000, hasil tersebut menunjukkan terdapat perbedaan tingkat pengetahuan sebelum dengan sesudah diberikan intervensi edukasi pencegahan HIV/AIDS melalui media tiktok dan terdapat perbedaan sikap sebelum dan sesudah diberikan intervensi edukasi pencegahan HIV/AIDS melalui media tiktok. Maka dapat disimpulkan bahwa adanya pengaruh edukasi pencegahan HIV/AIDS melalui media tiktok terhadap tingkat pengetahuan dan sikap siswa Jurusan Teknik Jaringan Komputer di SMK Muhammadiyah 3 Tangerang Selatan. Saran dari hasil penelitian ini diharapkan setelah diberikan edukasi kesehatan tentang HIV/AIDS agar para remaja bisa mendapatkan informasi yang baik dan melakukan pencegahan secara dini terhadap penyakit infeksi menular HIV/AIDS